Effect of annealing processing on microstructure and properties of Ti-6Al-4V alloy by powder injection molding - 郭世柏 曲选辉 向军淮 张荣发 何向明 李明升 多书旺 李文魁 (Transactions of Nonferrous Metals Society of China, 2006)
Ti6Al4V alloy parts were prepared by metal injection molding. Brown parts were densified at 1 200-1 260℃ for 2-4 h in vacuum atmosphere. The as-sintered specimens were treated through Hot-Isostatic Pressure（HIP） at 960 ℃ and 140 MPa. Ti6Al4V alloy compacts were annealed at 720-760 ℃ for 1 h. The results show that binder in the parts can be removed by solvent debinding and thermal debinding process. Ti6Al4V alloy has an uniform duplex microstructure with many equiaxed a grains and a little fl grains. When the annealing temperature is higher than 800 ℃, Ti6Al4V alloy has lower mechanical properties.After solution treatment and aging, a typical martensite microstructure can be achieved.